Evaluating strategies to reduce urban air pollution. (February 2016) - Duque, L.; Relvas, H.; Silveira, C.; Ferreira, J.; Monteiro, A.; Gama, C.; Rafael, S.; Freitas, S.; Borrego, C.; Miranda, A.I.
Abstract: During the last years, specific air quality problems have been detected in the urban area of Porto (Portugal). Both PM10 and NO2 limit values have been surpassed in several air quality monitoring stations and, following the European legislation requirements, Air Quality Plans were designed and implemented to reduce those levels. In this sense, measures to decrease PM10 and NO2 emissions have been selected, these mainly related to the traffic sector, but also regarding the industrial and residential combustion sectors. The main objective of this study is to investigate the efficiency of these reduction measures with regard to the improvement of PM10 and NO2 concentration levels over the Porto urban region using a numerical modelling tool – The Air Pollution Model (TAPM). TAPM was applied over the study region, for a simulation domain of 80 × 80 km 2 with a spatial resolution of 1 × 1 km 2 . The entire year of 2012 was simulated and set as the base year for the analysis of the impacts of the selected measures. Taking into account the main activity sectors, four main scenarios have been defined and simulated, with focus on: (1) hybrid cars; (2) a Low Emission Zone (LEZ); (3) fireplaces and (4) industry. The modelling results indicate that measures to reduce PM10 should be focused on residential combustion (fireplaces) and industrial activity and for NO2 the strategy should be based on the traffic sector. The implementation of all the defined scenarios will allow a total maximum reduction of 4.5% on the levels of both pollutants. Highlights: We investigate measures to reduce PM and NO2 ambient levels over Porto urban area. We use the TAPM numerical modelling tool. Measures for traffic sector, industry and residential combustion have been selected. To reduce PM10 measures should be focused on residential combustion and industry. For NO2 the strategy should be based on the traffic sector. Implementation of all scenarios allows a maximum reduction of 4.5% for both pollutants.